2023
DOI: 10.3390/su151410757
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Modern Wind Power Generation Forecasting Technologies

Abstract: The prediction of wind power output is part of the basic work of power grid dispatching and energy distribution. At present, the output power prediction is mainly obtained by fitting and regressing the historical data. The medium- and long-term power prediction results exhibit large deviations due to the uncertainty of wind power generation. In order to meet the demand for accessing large-scale wind power into the electricity grid and to further improve the accuracy of short-term wind power prediction, it is n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 139 publications
0
3
0
Order By: Relevance
“…Advancements in wind power-generation technologies are crucial for grid dispatching and energy distribution. Artificial intelligence techniques such as artificial neural networks (ANN) and support-vector machines (SVMs) have been widely used in wind energy forecasting [6,7]. The development of accurate and precise short-term wind power prediction models based on these advanced algorithms is necessary to accommodate large-scale wind power into the electricity grid.…”
Section: Introductionmentioning
confidence: 99%
“…Advancements in wind power-generation technologies are crucial for grid dispatching and energy distribution. Artificial intelligence techniques such as artificial neural networks (ANN) and support-vector machines (SVMs) have been widely used in wind energy forecasting [6,7]. The development of accurate and precise short-term wind power prediction models based on these advanced algorithms is necessary to accommodate large-scale wind power into the electricity grid.…”
Section: Introductionmentioning
confidence: 99%
“…Many methods have been proposed for WSP/WPP, which can be classified into several groups according to different classification criteria [9], as shown in Figure 2. According to the time scale [10], they are divided into ultra-short-term (a few seconds to 30 min ahead), short-term (30 min to 6 h ahead), medium-term (6 h to 1 day ahead) and long-term (1 day to 1 week or more ahead) models [11][12][13]. This classification reflects a focus on the time span of predictions and provides more specific time frameworks for different application scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the comprehensive, in-depth implementation of the dual-carbon plan, it can be observed that the development of power systems has been focused primarily on the advancement of new energy development, the significant improvement of energy utilization efficiency, and the optimization and upgrading of the energy consumption structure. Nevertheless, the year-on-year growth of new energy installed capacity and the comprehensive grid connection of large-scale regional new energy stations, as evidenced in the literature [1][2][3], indicate that the stochasticity and volatility of new energy outputs are gradually becoming a significant threat to system stability. Furthermore, the literature [4][5][6] the phenomenon of wind and light being abandoned.…”
Section: Introduction 1motivation and Related Workmentioning
confidence: 99%